Identification of likely foraging habitat of pelagic loggerhead sea turtles (Caretta caretta) in the North Atlantic through analysis of telemetry track sinuosity - McCarthy, Abigail L. (2021)
Changes in the behavior of individual animals in response to environmental characteristics can provide important information about habitat preference, as well as the relative risk that animals may face based on the amount of time spent in hazardous areas. We analyzed movement and habitat affinities of ten log gerhead turtles (Caretta caretta) tagged with satellite transmitters in the spring and fall of 1998 near Madeira, Portugal for periods of 2–10 months. We analyzed the behavior of these individuals in relation to the marine environment they occupied. As a measure of behavior we calculated the straightness index (SI), the ratio of the displacement of the animal to the total distance traveled, for individual weekly seg ments of the 10 tracks. We then extracted information about chlorophyll a concentration, sea-surface temperature (SST), bathymetry, and geostrophic current of the ocean in a 20-km buffer surrounding the tracks, and examined their relationship to the straightness index using generalized linear models. Chlorophyll a value, bathymetry and SST were significantly related to the straightness index of the tracks of all ten animals, as was the circular standard deviation of the geostrophic current (Wald’s test: p = 0.001, p = 0.008, p = 0.025, and p = 0.049, respectively). We found a significant negative relationship between straightness index and chlorophyll, and positive relationships with ocean depth and SST indicat ing that animals are spending more time and searching more thoroughly in areas with high chlorophyll concentrations and in areas that are shallower, while moving in straight paths through very warm areas. We also found a positive relationship between straightness index and the circular standard deviation of surrounding geostrophic currents suggesting that these turtles are more likely to move in a straight line when in the presence of diffuse, less-powerful currents. Based on these relationships, we propose that conservation planning to reduce overlap of turtles with fishing operations should take into account the locations of bathymetric features such as seamounts and upwelling locations where chlorophyll concen trations are high. This analysis is an effective way to characterize areas of high-use habitat for satellite tagged marine vertebrates, and allows for comparisons of these characteristics between species and among individuals.